LINGUISTIC ANALYSIS OF ALEXANDER FEINBERG'S POEMS (Ustozlar uchun, 2025)
This article provides information about the poetry of Alexander Feinberg, a talented artist of the Uzbek and Russian people.  Also, his poems are analyzed linguistically.